Evaluating the travel demand using E-bike on campus - Norhisham S.; Bakar M.F.A.; Huri A.H.; Mohammad A.; Khalid N.H.N.; Basri H.; Mardi N.H.; Zaini N. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Nowadays, Malaysia is facing real problem on traffic issues such as traffic congestion, deficiency of land for parking space and increasing vehicle volume. Cycling is one of alternative approach of transportation to overcome traffic issues. This objective of this study is to forecast the travel demand using E-bike in University and comparison of carbon footprint reduces between E-bikes and motorize vehicle. UNITEN has launched a program called Electric Palled-Assisted Biked (EPAB) as topromotes the usage of E-Bikes as their main mode of transportation in UNITEN Putrajaya campus. All the travellingdata have been recording using Application Strava. The CO2 emission and fuel cost for those particular tripshave also addressed in these studies.The result found that 107.27 daily trips were generated by E-bikes in UNITEN Putrajaya campus. The study also found that 88 percent of CO2emission is reduced when substituting car with E-bikes. An astonishing 560.918kg of CO2 was prevented from releasing to the atmosphere. Cycling has been proven as one of alternative option in developed countries to reduce the vehicle volume on the road. Further studies on these topic is highly recommend by increasing the number of participant in future. BEIESP.